Gender Transformation through Cultural Globalization in Urban Makassar amid Youth Activism and Generational Resistance - Latif, Muchtazar; Alam, Syamsul; Ananda, Rifki (Journal Social Humanity Perspective, 2024)
The concept of uncharted implications of cultural globalization on gender conventions, in the forms of intergenerational and institutional shifts, is the qualitative research problem of the study. Based on the literature of management, it focuses on two issues: how the transnational impact of cultural forces rearticulates local notions of gender, especially in the younger generations, and how older generations respond negatively to changes. Based on the evidence of Indonesia urban people, the study illustrates how hybrid gender features have been developed using media circulation and transnational feminism discursive frameworks. The young people here are instruments of cultural change who rebel against the patriarchal framework and openly encourage the relaxation of gender definitions within the social and the corporate context as well. On the other hand, the older generations feel threatened by these changes in terms of social order. Gender, as a complex dynamic and negotiated construct, is presented as an issue of intersectional tension and tension, which plays an important role in managing practice, especially in human resources, workplace equity and leadership roles. The paper also ends with the recommendation that culturally sensitive management approaches that cut across generations and advocate an inclusive gender practice should be promoted. It appeals to the transformation of gender in management as an ever-changing power, as opposed to a fixed identity and requests adaptive and reflexive paradigms of organization.